Analisis Kepatuhan Syariah Implementasi Prinsip Bagi Hasil pada Simpanan Mudharabah di KSPPS Binamas Purworejo - Soim Khudori (At-Tauzi : Jurnal Ekonomi Islam, 2019)
The result is a branding on the savings product (Tabungan) in Syariah Bank and the cooperative Save Sharia Financing (KSPPS). There are two principles of distribution of business results that are declared by the National Sharia Council (DSN) can be implemented, namely Profit Sharing and Revenue Sharing.This research aims to reviewing the aspect of sharia compliance for the distribution of the Mudharabah stale of deposits in KSPPS Binamas Purworejo using the principle of Profit Sharing. The Sharia reference used in this research is Fatwa No. 15/DSN-MUI/IX/2000 and PSAK No. 105 Article 11.This type of research is a qualitative descriptive with the methods of data collection interviews and documentation studies. The analysis tool uses comparation approach, by comparing the accounting structure for the calculation of the results on KSPPS Binamas with Sharia reference in this research. The results found that the calculation of distribution for the results on Mudharabah deposits in KSPPS Binamas Purworejo Sharia compliant or has fulfilled Sharia compliance.